Evaluación del comportamiento agronómico de líneas promisorias de cebada (hordeum vulgare l.) dística del iniap bajo condiciones agroecológicas del Campus Salache UTC 2021 – 2022. - Lasluisa Toasa, Jessica Estefanía (2022)
The present research emphasizes the adaptability of four promising lines (CMU – 19 – 001, CMU – 19 – 002, CD – 19 – 004 and CD – 19 – 013) and an improved variety (INIAP – CAÑICAPA 2003) of barley dística, through the support of the National Institute of Agricultural Research (INIAP) had the objective of evaluating the agronomic behavior of advanced barley lines (Hordeum vulgare L.) INIAP statistics under the agroecological conditions of the Technical University of Cotopaxi – Salache Campus, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province 2021 - 2022. A Completely Random Block Design (DBCA) was used that has 5 treatments and 3 repetitions, which were planted in plots of 3.6 square meters. In addition, during the vegetative cycle the following morphological parameters were evaluated: flowering days, plant height, number of spikes per square meter, spike size, number of grains per spike, grain yield, weight of a thousand grains, hectolitric weight. Concluding that under the environmental conditions of the Campus – Salache the promising line CD-19-013 presented a better agronomic behavior compared to the new variety. This line presented optimal values in the percentage of germination with a value of 99%, a plant height of 111.45 cm, the spike size was 11.28 cm and 27 grains per spike were obtained.